The Spenser encyclopedia - Hamilton, A. C. (Albert Charles), 1921-2016 (University of Toronto Press, 1990)
Encyclopedia covers aspects of literature and society in Elizabethan England.
Keywords: Spenser, Edmund, -- 1552?-1599 -- Encyclopedias.; Spenser, Edmund, -- 1552?-1599 -- Encyclopédies.; Spenser, Edmund, -- 1552?-1599; Spenser, Edmund -- 1552-1599; Spenser, Edmund.; Poets, English -- Early modern, 1500-1700 -- Biography -- Encyclopedias.; Great Britain -- Civilization -- 16th century -- Encyclopedias.; Grande-Bretagne -- Civilisation -- 16e siècle -- Encyclopédies.; LITERARY CRITICISM -- Shakespeare.; HISTORY -- Renaissance.; POETRY -- English, Irish, Scottish, Welsh.; Civilization; Poets, English; Poets, English -- Early modern; Great Britain; Wörterbuch; English poetry; e-books.; encyclopedias.; Reference works; Encyclopedias; Encyclopedias.; Reference works.; Livres numériques.; Ouvrages de référence.; Encyclopédies.